2022
DOI: 10.12688/wellcomeopenres.18050.1
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposures to fine particulate matter and carbon monoxide in relation to cooking activities in rural Malawi

Abstract: Background: Air pollution is a major environmental risk factor for cardiorespiratory disease. Exposures to household air pollution from cooking and other activities, are particularly high in Southern Africa. Following an extended period of participant observation in a village in Malawi, we aimed to assess individuals’ exposures to fine particulate matter (PM2.5) and carbon monoxide (CO) and to investigate the different sources of exposure, including different cooking methods. Methods: Adult residents of a vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The positive association can be explained from the perspective that the combustion of unclean cooking fuels produces high levels of indoor air pollution, including fine particulate matter (<2.5 μm), carbon monoxide and nitrogen oxides. 30 , 31 Exposure to these pollutants has been linked to an increased risk of hypertension by promoting oxidative stress, inflammation and endothelial dysfunction. 32 , 33 Therefore, our findings underscore a need for SSA countries to intensify current actions to reduce the reliance on unclean cooking fuel at the household and population level.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association can be explained from the perspective that the combustion of unclean cooking fuels produces high levels of indoor air pollution, including fine particulate matter (<2.5 μm), carbon monoxide and nitrogen oxides. 30 , 31 Exposure to these pollutants has been linked to an increased risk of hypertension by promoting oxidative stress, inflammation and endothelial dysfunction. 32 , 33 Therefore, our findings underscore a need for SSA countries to intensify current actions to reduce the reliance on unclean cooking fuel at the household and population level.…”
Section: Discussionmentioning
confidence: 99%
“…Most income came from ad hoc piece work or self-employment in small businesses. Cooking, mainly carried out by female household members, constituted the main source of PM 2.5 exposure in this setting 26 . Across the village, most cooking was done on three-stone fires, using collected firewood for fuel.…”
Section: Study Setting and Populationmentioning
confidence: 94%
“…As in the baseline study 26 , on monitor collection, memory cards were removed and the data used to create simple line graphs on a laptop, which were then viewed together, by the participant and researcher, and used as a basis for activity recall. This technique (developed on the basis of earlier work using monitoring alongside participant observations), allowed for division of all traces into 'background' periods of no identified exposure, and periods of 'activity' (where a specific source of combustion was identified).…”
Section: Data Collectionmentioning
confidence: 99%
“…Indoor pollution is prevalent in rural Malawi, where most households use firewood or charcoal for cooking, candles, and kerosene lamps for light [10,11]. A quantitative study [8] of 20 participants in a rural village in South Malawi found that firewood and charcoal cooking exposed villagers to fine particulate matter (PM 2.5 ) greater than 1000 µg/m 3 , which is a hundred times higher than the WHO recommended limit of 10 µg/m 3 . Given such findings, it is unsurprising that air pollution caused an estimated 12,400 deaths in Malawi in 2019 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked deforestation in sub-Saharan Africa (SSA) to the continued use of firewood and charcoal, particularly for cooking, which increases the rate of deforestation and forest degradation in the region [2,5,7,8]. With one of the lowest levels of access to clean cooking at 1%, Malawi has one of the highest deforestation rates in SSA, estimated at 2.8% per year [1,9].…”
Section: Introductionmentioning
confidence: 99%